Rehabilitation of homonymous hemianopia: insight into blindsight - Perez, Céline; Chokron, Sylvie (Frontiers in Integrative Neuroscience, 2014)
Strong evidence of considerable plasticity in primary sensory areas in the adult cortex, and of dramatic cross-modal reorganization in visual areas, after short- or long-term visual deprivation has recently been reported. In the context of patient rehabilitation, this scientifically challenging topic takes on urgent clinical relevance, especially given the lack of information about the role of such reorganization on spared or newly emerged visual performance. Amongst the most common visual field defects found upon unilateral occipital damage of the primary visual cortex is homonymous hemianopia (HH), a perfectly symmetric loss of vision in both eyes. Traditionally, geniculostriate lesions were considered to result in complete and permanent visual loss in the topographically related area of the visual field (Huber, 1992). However, numerous studies in monkeys, and later, in humans, have demonstrated that despite destruction of the striate cortex, or even following a hemispherectomy, some patients retain a certain degree of unconscious visual function, known as blindsight. Accordingly, there have recently been attempts to restore visual function in patients by stimulating unconscious preserved blindsight capacities. Herein we review different visual rehabilitation techniques designed for brain-damaged patients with visual field loss. We discuss the hypothesis that explicit (conscious) visual detection can be restored in the blind visual field by harnessing implicit (unconscious) visual capacities. The results that we summarize here underline the need for early diagnosis of cortical visual impairment (CVI), and the urgency in rehabilitating such deficits, in these patients. Based on the research precedent, we explore the link between implicit (unconscious) vision and conscious perception and discuss possible mechanisms of adaptation and plasticity in the visual cortex.